Efficacy of Rebamipide in Organic and Functional Dyspepsia: A Systematic Review and Meta-Analysis - Jaafar, Mohamed Hasif; Safi, Sher Zaman; Tan, Maw Pin; Rampal, Sanjay; Mahadeva, Sanjiv (Springer, 2018)
Objective: The role of gastritis in dyspepsia remains controversial. We aimed to examine the efficacy of rebamipide, a gastric mucosal protective agent, in both organic and functional dyspepsia. Design: A systematic review and meta-analysis was performed. The following databases were searched using the keywords (“rebamipide” OR “gastroprotective agent*” OR “mucosta”) AND (“dyspepsia” OR “indigestion” OR “gastrointestinal symptoms”): PubMed, Wed of Science, Embase, CINAHL, Cochrane Clinical Trials Register. The primary outcome was dyspepsia or upper GI symptom score improvement. Pooled analysis of the main outcome data were presented as risk ratio (RR) for dichotomous data and standardized mean difference (SMD) for continuous data. Results: From an initial 248 records, 17 randomised controlled trial (RCT) publications involving 2170 subjects (1224 rebamipide, 946 placebo/control) were included in the final analysis. Twelve RCTs were conducted in subjects with organic dyspepsia (peptic ulcer disease, reflux esophagitis or NSAID-induced gastropathy) and five RCTs were conducted in patients with functional dyspepsia (FD). Overall, dyspepsia symptom improvement was significantly better with rebamipide compared to placebo/control drug (RR 0.77, 95% CI = 0.64–0.93; SMD −0.46, 95% CI = −0.83 to −0.09). Significant symptom improvement was observed both in pooled RR and SMD in subjects with organic dyspepsia (RR 0.72, 95% CI = 0.61–0.86; SMD −0.23, 95% CI = −0.4 to −0.07), while symptom improvement in FD was observed in pooled SMD but not RR (SMD −0.62, 95% CI = −1.16 to −0.08; RR 1.01, 95% CI = 0.71–1.45). Conclusion: Rebamipide is effective in organic dyspepsia and may improve symptoms in functional dyspepsia.